Analysis Of Methods For Identifying And Describing Literary Motifs - Zamira Ayimbetova (Zien Journals, 2024)
This article examines various methods for identifying and classifying literary motifs, emphasizing the importance of motifs in interpreting literary texts. Motifs, as recurring elements, provide structural and symbolic foundations for narratives and reflect cultural, social, and psychological characteristics of their time. By exploring several approaches – including historical-cultural, structural, semiotic, psychoanalytic, and intertextual methods – the article presents a comprehensive system for identifying and analyzing motifs from different literary traditions. A classification system based on themes, symbolism, and archetypes is proposed, supported by detailed examples from classical and modern literature. This integrative framework aims to improve our understanding of literary motifs and their functions within a broader cultural context.
Keywords: Literary Motifs; Narrative Structure; Archetypes; Symbolism